2003
DOI: 10.1046/j.1468-2982.2003.00465.x
|View full text |Cite
|
Sign up to set email alerts
|

Cranial and Peripheral Interictal Vascular Changes in Migraine Patients

Abstract: As migraine is associated with an increased risk for ischaemic stroke and peripheral vasospastic disorders, it was hypothesized that interictal vascular changes may be present in migraine patients. Using ultrasound and applanation tonometry, the cardiovascular properties of migraine patients were compared with those of matched control subjects. Vascular parameters of the carotid arteries, cardiac output and systemic vascular resistance did not differ between both groups. Right temporal artery diameter was larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
2
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 45 publications
3
52
2
2
Order By: Relevance
“…However, arterial stiffness is also determined by vessel wall structure. de Hoon et al (20) have shown higher intima-media thickness in the brachial artery in middle-aged migraine patients. Elevated serum elastase activity has also been reported in migraine subjects (36).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, arterial stiffness is also determined by vessel wall structure. de Hoon et al (20) have shown higher intima-media thickness in the brachial artery in middle-aged migraine patients. Elevated serum elastase activity has also been reported in migraine subjects (36).…”
Section: Discussionmentioning
confidence: 95%
“…( 19 ) reported that migraine attacks are accompanied by generalized peripheral vasoconstriction. Furthermore, migraine patients have displayed increased diameter and/or decreased distensibility of cranial and peripheral blood vessels even in the interictal period ( 20 ). These observations indicate the importance of vascular properties in the link between migraine and ischemic stroke.…”
Section: Introductionmentioning
confidence: 91%
“…Thus, only the effect of inflammation on vascular structures with underlying migraine was assessed using CIMT following the exclusion of any factors that may have influenced the CIMT measurements. In the studies by Hoon et al and Iversen et al, it was reported that the vascular changes that occur during a migraine attack are not only confined to the cerebral vessels; there is also diffuse peripheral vasoconstriction, suggesting that migraines represent a generalized vascular disorder [30,31]. Moreover, in a study on patients with migraines aged 20-40 years, Besir et al reported that CIMT values were significantly higher when compared to controls.…”
Section: Discussionmentioning
confidence: 98%
“…In sCAD an altered carotid artery distensibility was found [131] and the endothelium-dependent vasodilatation of brachial artery is also hampered [132]. These vessel alterations are comparable to those observed interictally in migraineurs [133,134]. The appearance of sCAD may have a genetic background [135,136], suggesting that inherited variations of the extracellular matrix could be the common link for both conditions, altering the regulation of the endothelial and vascular functions [137][138][139].…”
Section: Connection Between Migraine and Strokementioning
confidence: 66%